Dendritic cells from human tissues express receptors for the immunoregulatory vitamin D3 metabolite, dihydroxycholecalciferol. - Brennan, A (1987)
Dendritic cells have been isolated from human tonsillar tissue and shown to act as accessory cells in a mitogenic response. The dendritic cells will induced receptors for the active metabolite of vitamin D3, 1,25(OH)2D3, in the responder E+ T cells. The dendritic cells themselves constitutively express receptors for the metabolite, and this distinguishes them from other non-T cells in lymphomedullary tissue. Expression of the 1,25(OH)2D3 receptor may be a dendritic cell property that facilitates their accessory cell role within the tissue microenvironment.